Systems Pharmacology Based Strategy for Q-Markers Discovery of HuangQin Decoction to Attenuate Intestinal Damage - Xiao-min Dai; Xiao-min Dai; Dong-ni Cui; Dong-ni Cui; Jing Wang; Wei Zhang; Zun-jian Zhang; Zun-jian Zhang; Feng-guo Xu; Feng-guo Xu (Frontiers Media S.A., 2018)
The quality control research of traditional Chinese medicine (TCM) is lagged far behind the space of progress in modernization and globalization. Thus the concept of quality marker (Q-marker) was proposed recently to guide the quality investigations of TCM. However, how to discover and validate the Q-marker is still a challenge. In this paper, a system pharmacology based strategy was proposed to discover Q-marker of HuangQin decoction (HQD) to attenuate Intestinal Damage. Using this strategy, nine measurable compounds including paeoniflorin, baicalin, scutellarein, liquiritigenin, norwogonin, baicalein, glycyrrhizic acid, wogonin, and oroxylin A were screened out as potential markers. Standard references of these nine compounds were pooled together as components combination according to their corresponding concentration in HQD. The bioactive equivalence between components combination and HQD was validated using wound healing test and inflammatory factor determination experiment. The comprehensive results indicated that components combination is almost bioactive equivalent to HQD and could serve as the Q-markers. In conclusion, our study put forward a promising strategy for Q-markers discovery.